Peran Masyarakat Dalam Pengembangan Objek Wisata Religi Masjid Cheng Hoo Di Kota Palembang - Oktisari, Dwi (LP3M IAI Al-Qolam, 2024)
In the golden age of Sriwijaya, Palembang was a center for learning Buddhism. After being destroyed, the era of the sultanate emerged and became the center of Islamic intellectualism. This is marked by the presence of scholars who have authority in the field of religion. Therefore, in Palembang, a religious tourism object was established, namely the Cheng Hoo Mosque which is famous for its combination of Malay and Chinese nuances. However, the mosque has not fully become one of the superior tourist attractions even though efforts have been made through da'wah strategies and improving mosque facilities. This study aims to determine the role of the community in developing the Cheng Hoo Mosque religious tourism object in Palembang. The method used is a descriptive qualitative approach using secondary data sources. Data collection techniques are carried out through literature studies and documentation. The results obtained include the establishment of the Cheng Hoo Mosque in Palembang cannot be separated from the role of Chinese Muslims in Palembang through PITI organization. In addition, the community has so far tried to participate in the development of this tourist attraction by maintaining cleanliness and cooperation with various agencies.